PENGARUH TENIK COMPREHENSIVE MODELLING TERHADAP MUTU LINGUISTIS, RETORIKA DAN MEKANIS PADA ARTIKEL JURNAL PENELITIAN MAHASISWA - Sujito Sujito; Mujiono Mujiono; Wildan Mahir Muttaqin (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study was intended to test the differences between the students who were given comprehensive modeling and those who are not given comprehensive modeling concerning with their achievement of Scientific Journal Writing in English Educational Department of IAIN Surakarta. The sample consists of 34 students randomly selected from the population. Data were collected by administering the writing test and analyzed by correlated sample t-test. The result revealed that there was a significant difference between students who were given comprehensive modeling and those who were not given comprehensive modeling in their achievement of Scientific Journal Writing in English Educational Department of IAIN Surakarta. It was derived that p=.000 >.005. So, the alternate hypothesis stating that the EFL students who were given comprehensive modeling have higher achievement in Scientific Journal Writing than those given conventional method was accepted. It means that the comprehensive modeling is an effective way to develop students' achievement in Scientific Journal Writing in English Educational Department of IAIN Surakarta.